Bioavailability and Dissolution Rate Enhancement of an Anticancer Drug Bicalutamide by Encapsulation into Mesoporous Silica Nanoparticles: Effects of Amine Functionalization and Caco-2 Cell Permeability Study - Saroj, Seema; Rajput, Sadhana (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: The present study was undertaken with the aim of dissolution rate and Bioavailability enhancement of anticancer drug Bicalutamide (BIC) via encapsulation into mesoporous silica nanoparticles (MSNs). Materials and Methods: The bare (MCM-41) and surface decorated MSNs were subjected to thorough characterization pre and post drug loading by Fourier transform infrared spectroscopy, Nitrogen sorption analysis, Differential Scanning Calorimetry, Thermogravimetric analysis, Small angle and wide angle X-ray diffraction, Scanning electron microscopy and Transmission electron microscopy. Introduction of Nitrogen post functionalization was confirmed by the elemental analysis. Synthesized MSNs were surface decorated with amine groups (AMN-MSN) and in-depth study of effect of functionalization and food on dissolution kinetics was done. Developed MSNs and AMN-MSNs were thoroughly characterized pre and post BIC loading. In vitro intestinal permeability study was performed to determine the apparent permeability of synthesized MSNs. The formulations were also investigated for their in vivo behaviour by oral administration to male Swiss albino mice and various pharmacokinetic parameters calculated. Results: A significant increase in permeability was obtained the dissolution rate and bioavailability were found to be 3.12 and 2.71 times enhanced in MCM-41 as comparison to the BIC suspension. Conclusion: Thus, MSNs could serve as an effective platform for delivering of various anti-cancer drugs and enhancing their efficiency.
Keywords: Bicalutamide; Functionalized Mesoporous silica nanoparticles; Dissolution; Caco-2 cells permeability; Bioavailability